ANALISIS KELAYAKAN USAHA DAN STRATEGI PENGEMBANGAN BUDIDAYA RUMPUT LAUT DI KABUPATEN SERAM BAGIAN BARAT - Aziz Ely; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2014)
The objectives of this study are to find out th level of business feasibility for seaweed cultivation and setting the strategy development business of seaweed cultivation in West Seram regency.Purposive sampling method was applied in this study for selecting locations in the district as center of seaweed production. West Seram Kotania, Osi Island, Wael hamlet, Wae Pesy, and Taman Jaya were selected as region fotr this study.From the location of the study, there were 47 respondents were selected by stratified random sampling for the SWOT analysis, composed as fisherman 40 respondents, fisher and nayal official 6, and 1 collectors.Data analysis was carried out to look at the business feasibility and development strategy in seaweed cultivation. Feasibiility analysis, namely Revenue Cost Ratio (R/C), Benefit Cost Ratio (B/C), Break Event Point (BEP) and Internal Rate of Investment (ROI) were applied. Moreover, to formulate the development strategy, the SWOT analysis instrument was used, which begins with the validity and reliability of the statement used in the SWOT analysis.Based on the analysis there were obtained that value of Revenue Cost Ratio (R/C>1) at 2.32, Benefit Cost Ratio (B/C>0) at 1.32, Break Event Point of price Rp 3,232.88, Break Event Point unit production of Rp 989.26 Kg, Rate of Investment (ROI) at 131,99%. From the analysis it can be concluded that the business development efforts of seaweed in the district of West Seram deserves to be developed. Then, SWOT analysis result shown that development strategy of seaweed farming is to reduce the intensity of cultivation, expansion, and increased production and maximizing the potential of local wisdom in the form of marine guard. Meanwhile, local governance should facilitate the development of seaweed production by serving coaches and supervision of seaweed farming.